2013
DOI: 10.1002/jsfa.6033
|View full text |Cite
|
Sign up to set email alerts
|

Equisetumarvense hydro‐alcoholic extract: phenolic composition and antifungal and antimycotoxigenic effect against Aspergillusflavus and Fusariumverticillioides in stored maize

Abstract: E. arvense extract could be an alternative to synthetic fungicides to control maize mycobiota level in moist grain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…The plant extract from Equisetum arvense (common horsetail), rich in flavonoids such as kaempferol (Fig. 2), has significant inhibition on Fusarium growth and could be used to control maize optimal cultivation and growth (29). Extracts from the trees Eysenhardtia texana (Texas kidneywood), Terminalia bellirica (bahera), and Hildegardia barteri contain the flavonoids hildegardiol, 2-hydroxymaackiain, and farrerol (Fig.…”
Section: Polyphenolsmentioning
confidence: 99%
“…The plant extract from Equisetum arvense (common horsetail), rich in flavonoids such as kaempferol (Fig. 2), has significant inhibition on Fusarium growth and could be used to control maize optimal cultivation and growth (29). Extracts from the trees Eysenhardtia texana (Texas kidneywood), Terminalia bellirica (bahera), and Hildegardia barteri contain the flavonoids hildegardiol, 2-hydroxymaackiain, and farrerol (Fig.…”
Section: Polyphenolsmentioning
confidence: 99%
“…Previous authors reported that ethanolic extracts from E. arvense induced anticancer effects to suppress lung carcinoma cells at 100–150 µg/mL [ 61 ]. Hydroethanolic extracts were more effective as antinociceptive and anti-inflammatory agents in mice [ 62 ] and had a negative influence on Aspergillus flavus and Fusarium verticillioides ; these produce mycotoxins in stored maize kernels ( Zea mays ) [ 63 ]. Aquatic extracts of E. arvense could possess antibacterial action toward clinical Escherichia coli involving the disruption of the biofilm formation [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of chromatographic profiles and spectroscopic characteristics of secondary metabolites present in extracts of plant origin with biological activity is essential to characterize them [34,35]. The characterization of the active plant extracts is the first step to perform the bio-guided fractionation for the activity and is also the reinsurance of the reproducibility of the activity.…”
Section: Discussionmentioning
confidence: 99%